2022
DOI: 10.3390/ijms23169133
|View full text |Cite
|
Sign up to set email alerts
|

Renin as a Marker of Tissue Perfusion, Septic Shock and Mortality in Septic Patients: A Prospective Observational Study

Abstract: Sepsis is a life-threatening organ dysfunction caused by the dysregulation of the host’s response to an infection, where the dominant mechanism is tissue hypoperfusion. Currently, the marker used to define tissue disorders is lactate levels, which may be elevated in other disease states as well. Renin is an essential hormone for the proper functioning of the renin-angiotensin-aldosterone (RASS) system. It is secreted in the glomerular apparatus in response to hypoperfusion. This study aimed to assess the usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Our search strategy identified a total of 2081 records. After screening, we included 16 studies with 1573 critically ill or perioperative patients (Figure) 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] with major exclusions and reasons for exclusion detailed in Supplemental Digital Content 1, Supplemental Table 1, http://links.lww.com/ AA/E504. Except for 2 studies, 16,21 the other 14 were published after 2017.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search strategy identified a total of 2081 records. After screening, we included 16 studies with 1573 critically ill or perioperative patients (Figure) 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] with major exclusions and reasons for exclusion detailed in Supplemental Digital Content 1, Supplemental Table 1, http://links.lww.com/ AA/E504. Except for 2 studies, 16,21 the other 14 were published after 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Except for 2 studies, 16,21 the other 14 were published after 2017. Shock (mainly vasodilatory or septic shock) was the most common etiology 11,12,15,18,20,21,23 and most of the included articles were prospective observational studies. 6,[12][13][14][15][16][17][18][20][21][22]24,25 The characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, renin has been proposed as a candidate biomarker in sepsis. Several post hoc and secondary analyses of randomized controlled trials, as well as observational studies, have reported associations between renin level or renin kinetics and sepsis outcomes (2–5). Renin is an upstream effector of the renin–angiotensin system (RAS) that converts angiotensinogen to angiotensin I, which is then converted to angiotensin II by the angiotensin-converting enzyme (ACE).…”
mentioning
confidence: 99%
“…A modest but growing number of studies suggest that renin may hold promise as a prognostic and predictive biomarker. Several studies have reported an association between elevated renin levels and adverse clinical outcomes, including mortality (2, 4, 5) or acute kidney injury (3, 5), in patients with sepsis. Some studies have suggested that renin levels may be more sensitive and specific than arterial lactate in predicting mortality (10).…”
mentioning
confidence: 99%